Does digital access translate into human capital gains? Assessing information technology use effects on cognitive and non-cognitive development of students in Western Rural China - Bin Tang; Zeming Cheng; Xiaoli Lin; Yunxuan Cao; Siyi Xiao; Yunhui Ma; Kaixuan Gao (PLoS ONE, 2026)
This study explores how the use of information technology (IT) influences the development of cognitive and non-cognitive abilities among primary school students in rural areas of western China. As IT tools become more integrated into daily life, especially in underdeveloped regions, their influence on education has grown significantly. Relying on Heckman’s human capital development theory, we apply Propensity Score Matching combined with a Difference-in-Differences (PSM-DID) approach to analyze two rounds of panel data collected from third and fourth grade students between 2019 and 2020. The analysis suggests that while IT use does not significantly boost cognitive skills, a slight positive trend is observed, likely reflecting the coexistence of both beneficial and adverse effects. In terms of non-cognitive skills, frequent IT use appears to enhance students’ openness and increase their fondness for school and teachers, yet it is also linked to rising levels of self-blame and anxiety. Additional findings show that the effects of IT use are more pronounced among older children, Han Chinese students, and those from households with lower income or lower parental education. These results contribute to a deeper understanding of IT’s role in shaping human capital in rural settings and offer practical implications for policymakers. In particular, they highlight the need to maximize the positive aspects of IT in promoting equity in education while addressing its potential downsides through more customized support for diverse student populations.